Differentiated Learning Using Canva: A Strategy for Enhancing Motivation and Learning Outcomes in Science Education - Triyono; Rakhmawati, Dini; Rasiman (Universitas Pendidikan Ganesha, 2024)
Student learning outcomes are influenced by various factors, one of which is the teaching method applied. In science education, the role of the teaching method is crucial in determining students' success in achieving the expected learning outcomes. However, the issue at hand is the lack of technology use in the classroom and the low motivation of fifth-grade students in engaging with lessons. This study aims to examine the impact of differentiated learning with Canva media on motivation and learning outcomes in science (IPAS) for fifth-grade students. This study employs a quasi-experimental design with a pretest-posttest and control group. The research involved 30 students, divided into two groups: 15 students in the intervention group and 15 students in the control group. Motivation and learning outcomes were measured using a validated and reliable questionnaire. Data were analyzed using paired T-tests and Independent Sample T-tests. The subjects' age ranged from 10 to 11 years. The results indicate a significant difference in the mean motivation difference between the intervention group (95.20±2.731) and the control group (87.07±5.725), with p = 0.000. Furthermore, there was a significant difference in the mean learning outcomes before and after the intervention in each group, with the intervention group achieving 84.33±3.716 (p = 0.000) and the control group achieving 70.67±8.209 (p = 0.003). The learning outcomes in the intervention group also showed a significant improvement compared to the control group (p = 0.000). The conclusion of this study is that differentiated learning using Canva media can significantly improve motivation and learning outcomes in fifth-grade students, making it an effective method for implementation in teaching.